Electrodeposited palladium on MWCNTs as 'semi-soluble heterogeneous' catalyst for cross-coupling reactions. Issue 27 (1st July 2015) - Radtke, Mariusz; Stumpf, Steffi; Schröter, Bernd; Höppener, Stephanie; Schubert, Ulrich Sigmar; Ignaszak, Anna
Graphical abstract: Highlights: Nano-sized Pd catalyst was electro-synthesized on MWCNTs from aqueous media. We recognized Pt-carbon electronic interaction by X-ray photoelectron spectroscopy. Pd-MWCNTs showed superior catalytic activity toward Suzuki–Miyaura and Sonogashira reactions. The Pd-MWCNTs can be recovered and re-used. Abstract: Platinum group metals (PGM) catalyze many important chemical processes including hydrogenation; electro-catalysis applied to fuel cell and battery technologies and one of the most prominent the Csp2 –Csp2 cross-coupling reactions such as Sonogashira, Suzuki–Miyaura, and Csp2 –Nsp3 cross-coupling as for the Buchwald–Hartwig type reactions. The main concern of the catalytic reaction is the recovery and recyclability of used catalytic entities. Recent efforts in the catalyst fabrication focus on combining a nano-sized metal with various high surface area supports like resins or carbon-based materials that allow recovering the catalyst after each reaction in a simple and convenient way. This work aims to investigate the catalytic activity of the carbon-supported (MWCNTs) electrodeposited metallic nanoparticles (Pd) and their applications in several cross-coupling reactions. We propose a simple and affordable synthesis of the high surface area Pd–C composite that can be re-used until deactivated. The intramolecular interactions between carbon and metallic fractions studied by X-ray photoelectron spectroscopy are discussed with respect to the catalytic efficiencies.